(untitled) (World of finance, 2021)
Introduction. In modern conditions of formation of priorities of the Ukrainian society in the context of sustainable development one of the priority tasks of the state is financial maintenance of realization of a social function. Therefore, a timely and urgent issue is the search for effective financial mechanisms for the implementation of the social function of the state to achieve national goals of sustainable development. The purpose of the article is to analyze of current trends and substantiation of the dominants of financial support of state social programs in the context of achieving the goals of sustainable development of Ukraine. Results. The study showed that an important role in achieving a positive social effect in the implementation of the Sustainable Development Goals of Ukraine belongs to the state target programs. State social programs focus on the implementation of measures for social support and basic social guarantees of the population. The value of targeted program funding is that it allows you to approach the solution of a social problem in a comprehensive way. A negative feature of targeted programs is the risk of funding on a residual basis. Conclusions. Financial support of state social programs should be considered as a set of forms and methods used in the distribution, redistribution and use of financial resources, which is formed from the State Budget of Ukraine, as well as other sources provided by law, and aims to solve problems level and quality of life, problems of unemployment, strengthening social protection, improving working conditions, development of health care and education, which contributes to the achievement of the Sustainable development goals of Ukraine.